An update on microbiological causes of canine otitis externa in Campania Region, Italy - Luisa De Martino; Francesca Paola Nocera; Karina Mallardo; Sandra Nizza; Eleonora Masturzo; Filomena Fiorito; Giuseppe Iovane; Piergiorgio Catalanotti (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To update the recent knowledge of the microbiological causes of canine otitis externa in Campania Region (Italy) and the antibiotic susceptibility patterns of the isolated strains. Methods: A total of 122 dogs were examined by otoscopy, and auricular swab samples were collected from both ears in 74 dogs presenting clinical bilateral otitis and from single ears in 48 dogs displaying clinical unilateral otitis. Cytological examination, bacteriological analysis and antimicrobial susceptibility tests were performed. Results: Thirty-one out of 122 dogs were positive for yeast species (25.4%, 95% confidence interval (CI): 18.2%–34.2%) with a higher prevalence of Malassezia pachydermatis (21/31 isolates, 67.7%, CI: 48.5%–82.7%), and a total of 91 out of 122 dogs were positive for bacterial species (74.6%; CI: 65.8%–81.8%) with a higher prevalence of Staphylococcus pseudintermedius (45/143 isolates, 31.5%, CI: 24.1%–39.8%). These results are the first description of Streptococcus agalactiae-associated otitis. The yeasts isolated showed high levels of susceptibility to all antifungal agents tested; on the contrary all the isolated bacterial strains were highly resistant to at least four out of ten antimicrobial classes. Both Gram-positive and Gram-negative bacteria showed high resistance to amoxicillin/clavulanate and kanamycin hence they are not recommended as initial empirical therapy for the otitis treatment. Conclusions: This update illustrates an increase in antibiotic resistances providing an insight into the current knowledge of the therapeutic procedures followed on canine otitis externa in Italy. It also emphasizes the importance of considering the results of the microbiological and sensitivity tests to decide on an appropriate antibiotic therapy.